2013
DOI: 10.1590/s0004-27492013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic avulsion of extraocular muscles: case reports

Abstract: We described the clinical, surgical details and results (motor and sensory) of the retrieving procedure of traumatically avulsed muscles in three patients with no pre vious history of strabismus or diplopia seen in the Department of Ophthalmolo gy, State University of Campinas, Brazil. The slipped muscle portion was reinserted at the original insertion and under the remaining stump, which was sutured over the reinserted muscle. For all three cases there was recovery of single binocular vision and stereopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The exact interval during which a muscle should be recovered to restore some functionality remains inconclusive. 24 When a rupture is suspected, some suggest immediate consideration of surgical exploration to avoid the sequelae of diplopia. 9,20 Muscles ruptured intraoperatively should be retrieved immediately for the best postoperative outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The exact interval during which a muscle should be recovered to restore some functionality remains inconclusive. 24 When a rupture is suspected, some suggest immediate consideration of surgical exploration to avoid the sequelae of diplopia. 9,20 Muscles ruptured intraoperatively should be retrieved immediately for the best postoperative outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…It is inconclusive the exact interval during which a muscle should be recovered with satisfactory function restoration (8) . Wright suggested a time limit as soon as 7-10 days after the traumatic event (9) , showing that this case, treated within 6 days of trauma, was included in the optimal time delay.…”
Section: Discussionmentioning
confidence: 99%
“…Prisms, chemodenervation with botox, and further surgeries may be required for a residual or consecutive tropia, so close follow up is essential. It is suggested that a reattachment procedure should be done at about 7-10 days after the injury for best results [14], in this case the repair was done on day 8 post injury, which lead to an outcome that the patient was happy with.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures adequate retraction which aids in identifi cation and manipulation of the lost muscle. An important tool in assisting with identifi cation of a lost muscle is the oculocardiac refl ex[6,7,12,14]. When pulling on the proximal stump of muscle one should illicit the oculocardiac refl ex causing a parasympathetic response and hence a bradycardia.…”
mentioning
confidence: 99%